PETA KOMPETENSI SISWA PADA UN MATA PELAJARAN EKONOMI-SMA DI KABUPATEN BIREUEN - Ruaida, Ruaida (Universitas Muhammadiyah Aceh, 2011)
This research aims to determine the basic competencies of what is problematic in the National Examination for Economic Subjects at secondary schools in Bireuen district. Another objective of this study is to determine the response of principal´s, economics teacher, and supervisor (stakeholders) about the causes of low student competence in each of the national examination result, as well as the recommended model for problem solving. The samples of this research are SMAN 1 Bireuen, SMAN 1 Jangka, and SMAN 1 Ganda Pura that are taken purposively. The data collection techniques used are documentation techniques, and focus group discussions (FGD) with stakeholders in each school. Data processing techniques used in this study is descriptive analysis. The results showed that there are 15 basic competitions that the accomplishments still have problems or<60 on the national exam of economic subjects in secondary school in the Bireuen district. This is due to the professional competence and teachers pedagogic for instance mastery of the material, how to motivate students, the use of methods, and instructional media, IT mastery,remainsproblematic. Another factor is the low awareness of parents in children´s learning process and school environments that have not been well ordered. In line with these factors, then the problem-solving model is the provision of the teachers professionalism training, such as stabilization of hard materials, stabilization of the pedagogic and IT mastery, and the provision of learning CD, it will be better if learning economics is hold in teams and involving at least two teachers in the study. In addition, it is needed for teacher to have assistance program in designing and implementing learning, and maximize the function of the school committee as a forum for parents to take care and contributeto the education of theirchildren. Key words: student competence, national exam in Economics Lesson DAFTAR PUSTAKA Badan Standar Nasional Pendidikan, 2006. Panduan Penyusunan Kurikulum Tingkat Satuan Pendidikan Jenjang Pendidikan Dasar dan Menengah. Jakarta Badan Standar Nasional Pendidikan, 2007. Petunjuk Teknis Pengembangan Silabus dan Contoh/Model Silabus Mata Pelajaran Ekonomi SMA/MA. Jakarta Departemen Pendidikan Nasional. Direktorat Jenderal Manajemen Pendidikan Dasar dan Menengah, 2006. Peraturan Menteri Pendidkan Nasional Repoblik Indonesia No 23 Tahun 2006 Tentang Standar Kompetensi Lulusan Untuk Satuan Pendidikan Dasar dan Menengah. Jakarta Departemen Pendidikan Nasional.2008. Perangkat pembelajaran KTSP SMA, Jakarta Departemen Pendidikan Nasional, 2008. Panduan Pengembangan Indikator, Jakarta Departemen Pendidikan Nasional DirektoratTenaga Kependidikan Direktorat Jenderal Peningkatan Mutu Pendidikdan Tenaga Kependidikan 2008.Strategi Pembelajaran dan Pemilihannya. Jakarta E. Mulyana, 2007. Kurikulum Tingkat Satuan Pendidikan (Sebuah Panduan Praktis). PT Remaja Rosda Karya Bandung Neti Budiawati, Leni Permana, 2010 Perencanaan Pembelajaran Ekonomi, Laboratorium Pendidikan Ekonomi dan Koperasi Universitas Pendidikan Indonesia, Bandung.